Efficacy and safety of antibody-drug conjugates for HER2-expressing advanced gastric and gastroesophageal junction adenocarcinoma: a systematic review and meta-analysis - Huang, Danxue; Sun, Feilong; Li, Su; Ke, Liyuan (Frontiers in Pharmacology, 2025)
BackgroundAntibody-drug conjugates (ADCs) represent a promising therapeutic modality for gastric cancer. Given the highly heterogeneous nature of this malignancy, the efficacy and safety profile of ADC treatment warrant comprehensive evaluation.MethodsA systematic search of online databases identified prospective trials published through June 2025. Pooled estimates for OS, PFS, ORR, DCR, and TRAEs were derived using a random-effects model. Subgroup analyses were performed, stratified according to HER2 status, primary tumor location, line of therapy, and use of combination treatment.ResultsA total of 1779 patients from 13 prospective trials (18 reports) were included. The pooled ORR was 67% (95% CI: 53%–82%) for first-line ADC therapy, 40% (95% CI: 29%–51%) for second-line regimens, and 27% (95% CI: 16%–38%) for third-line regimens. In second-line or later therapy, HER2-positive patients achieved a superior ORR relative to HER2-low subgroups (39%, 30%–47% vs. 25%, 11%–39%). The overall pooled median OS was 11.95 months (95% CI: 9.93-13.96), with a median PFS of 4.94 months (95% CI: 3.92-5.96). Stratification by line of therapy revealed a median OS of 19.67 months (95% CI: 15.79-23.55) for first-line versus 11.65 months (8.09-15.22) for second-line and 9.37 months (7.38-11.37) for third-line, with corresponding median PFS of 10.57 months (6.37-14.77) vs. 4.13 months (2.43-5.83) and 4.50 months (3.51-5.50) respectively. TRAEs occurred in 98% (95% CI: 96%–100%) of patients (any-grade), with grade 3–5 events in 60% (52%–69%).ConclusionThis meta-analysis establishes ADCs as a promising therapeutic approach for advanced gastric or gastroesophageal junction cancer (GC/GEJC), demonstrating efficacy in both HER2-positive and HER2-low patient populations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251066208, identifier CRD420251066208.